Covid-19 Vaccine Diplomacy and Cultures of Anarchy in The International System - Ramdhan Muhaimin; Rizal A Hidayat; Eldha Mulyani (Sekretariat Jenderal DPR RI, 2021)
To fight the Covid-19 pandemic, several countries, through their pharmaceutical companies, conduct research and production of vaccines. Efforts to invent a vaccine are racing with the rapid mutation of Covid-19. The World Health Organization with GAVI (Global Alliance for Vaccines and Immunization) and CEPI (Coalition for Epidemic Preparedness Innovations) initiated a collaborative forum called Covid-19 Vaccine Global Access (COVAX). The goal there is justice and equity in the distribution of vaccines throughout the world. Although strategic efforts to deal with the Covid-19 pandemic are carried out multilaterally through COVAX, many countries have also taken bilateral steps to get their vaccine needs. On the other hand, the Covid-19 vaccine diplomacy that took place in an anarchic international system showed three different cultural patterns, namely Hobbesian (conflictual), Lockean (competitive), and Kantian (cooperative). By using a qualitative approach, this study analyzes three cultural patterns of anarchy in vaccine diplomacy. Data collection techniques in this research are based on library research. The theory used in this research is diplomacy and cultures of Anarchy in Constructivism approach. From this research, it was found that the COVAX is a representation of the cooperative pattern carried out by countries in overcoming the Covid-19 pandemic. But apart from that, there is also Hobbesian or conflictual diplomacy between the United States and China. Meanwhile, competitive diplomacy can be seen in the competition among vaccine-producing countries.AbstrakUntuk mengatasi pandemi Covid-19, sejumlah negara melalui perusahaan farmasinya melakukan penelitian dan produksi vaksin. Upaya pencarian vaksin berlomba dengan mutasi Covid-19 yang cepat. Organisasi Kesehatan Dunia (World Health Organization) bersama GAVI (Global Alliance for Vaccines and Immunization) dan CEPI (Coalition for Epidemic Preparedness Innovations) menginisiasi wadah kolaboratif bernama Covid-19 Vaccine Global Access (COVAX). Tujuannya, agar terjadi keadilan dan pemerataan dalam distribusi vaksin ke seluruh dunia. Meski upaya strategis menghadapi pandemik Covid-19 dilakukan secara multilateral melalui COVAX, tapi langkah-langkah bilateral juga banyak dilakukan negaranegara dalam memenuhi kebutuhan vaksinnya. Pada sisi lain, diplomasi vaksin Covid-19 yang terjadi dalam sistem internasional yang anarki menunjukkan tiga pola budaya yang berbeda, yaitu Hobbesian (konfliktual), Lockian (kompetitif), dan Kantian (kooperatif). Dengan menggunakan pendekatan kualitatif, penelitian ini menganalisis tiga pola budaya anarki dalam diplomasi vaksin yang terjadi saat ini. Tekni pengumpulan data pada penelitian berdasarkan riset kepustakaan (library research). Teori yang digunakan dalam penelitian ini adalah Diplomasi dan Budaya Anarki dalam Konstruktivisme yang dikembangkan Alexander Wendt. Dari penelitian ini, ditemukan wadah COVAX merupakan representasi pola kooperatif yang dilakukan negara-negara dalam mengatasi pandemik Covid-19. Namun selain itu, terjadi juga diplomasi ala Hobbesian atau konfliktual seperti yang terjadi antara Amerika Serikat dan China. Sedangkan diplomasi yang bersifat kompetitif terlihat pada persaingan di antara negara-negara produsen vaksin.